The Effect of the Phonics Method with Alphabet Songs on the Language and Cognitive Abilities of Children Aged 5-6 Years - Latifah, Nurul; Setyowati, Sri; Khotimah, Nurul (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the effect of the phonics method combined with alphabet songs on the language and cognitive abilities of 5-6 year old children at Yapita Kindergarten, Surabaya. This study used an experimental design with a quantitative approach, where the sample consisted of 30 children divided into two groups: a control group and an experimental group. The experimental group received treatment in the form of phonics methods with alphabet songs for 4 weeks, while the control group was not given treatment. The data were analyzed using an independent t-test to compare language and cognitive abilities between the two groups. The results showed a significant difference between the control group and the experimental group (p <0.05), where the experimental group experienced a significant increase in language and cognitive abilities after receiving treatment. The use of the phonics method combined with alphabet songs has proven effective in improving the language and cognitive skills of 5-6 year old children at Yapita Kindergarten. Therefore, this method is recommended for use in learning in early childhood education to support children's language and cognitive development optimally.